Peter Heine: Food Culture in the Near East, Middle East and North Africa & Colleen Taylor Sen: Food Culture in India & Fabio Parasecoli: Food Culture in Italy & Jacqueline M. Newman: Food Culture in China & Laura Mason: Food Culture in Great Britain - Chatterton, Lynne (Petits Propos Culinaires, 2005)
Peter Heine: Food Culture in the Near East, Middle East and North Africa: ISBN 0313329567: 181 pp. Colleen Taylor Sen: Food Culture in India: ISBN 0313324875: 197 pp. Fabio Parasecoli: Food Culture in Italy: ISBN 0313327262: 229 pp. Jacqueline M. Newman: Food Culture in China: ISBN 0313325812: 230 pp. Laura Mason: Food Culture in Great Britain: ISBN 031332798X: 238 pp. The Series Editor is Ken Albala of the University of the Pacific; the publisher is Greenwood Press, CT (www.greenwood.com), the books are distributed in England (priced £28) via Greenwood Publishing, P.O. Box 384 Halley Court, Jordan Hill, Oxford OX2 8RY.